BDNF val66met polymorphism influences age differences in microstructure of the corpus callosum - Kennedy, Kristen M.; Rodrigue, Karen M.; Land, Susan J.; Raz, Naftali (Frontiers in Human Neuroscience, 2009)
Brain-derived neurotrophic factor (BDNF) plays an important role in neuroplasticity and promotes axonal growth, but its secretion, regulated by a BDNF gene, declines with age. The low-activity (met) allele of common polymorphism BDNF val66met is associated with reduced production of BDNF. We examined whether age-related reduction in the integrity of cerebral white matter depends on the BDNF val66met genotype. Forty-one middle-aged and older adults participated in the study. Regional white matter integrity was assessed by fractional anisotropy (FA) computed from manually drawn regions of interest in the genu and splenium of the corpus callosum on Diffusion Tensor Imaging scans. After controlling for effects of sex and hypertension, we found that only the BDNF 66met carriers displayed age-related declines in the splenium FA, whereas no age-related declines were shown by BDNF val homozygotes. No genotype-related differences were observed in the genu of the corpus callosum. This finding is consistent with a view that genetic risk for reduced BDNF affects posterior regions that otherwise are considered relatively insensitive to normal aging. Those individuals with a genetic predisposition for decreased BDNF expression may not be able to fully benefit from BDNF-based plasticity and repair mechanisms.